Circulating Serum MicroRNA-130a as a Novel Putative Marker of Extramedullary Myeloma - Besse, Lenka; Sedlarikova, Lenka; Kryukov, Fedor; Nekvindova, Jana; Radova, Lenka; Slaby, Ondrej; Kuglik, Petr; Almasi, Martina; Penka, Miroslav; Krejci, Marta; Adam, Zdenek; Pour, Ludek; et al. (PloS one, 2015)
Poor outcome of extramedullary disease in multiple myeloma patients and lack of outcome predictors prompt continued search for new markers of the disease. In this report, we show circulating microRNA distinguishing multiple myeloma patients with extramedullary disease from myeloma patients without such manifestation and from healthy donors. MicroRNA-130a was identified by TaqMan Low Density Arrays and verified by quantitative PCR on 144 serum samples (59 multiple myeloma, 55 myeloma with extramedullary disease, 30 healthy donors) in test and validation cohorts as being down-regulated in myeloma patients with extramedullary disease. Circulating microRNA-130a distinguished myeloma patients with extramedullary disease from healthy donors with specificity of 90.0% and sensitivity of 77.1%, patients with extramedullary disease from newly diagnosed multiple myeloma patients with specificity of 77.1% and sensitivity of 34.3% in the test cohort and with specificity of 91.7% and sensitivity of 30.0% in the validation cohort of patients. Circulating microRNA-130a in patients with extramedullary myeloma was associated with bone marrow plasma cells infiltration. Further, microRNA-130a was decreased in bone marrow plasma cells obtained from patients with extramedullary myeloma in comparison to bone marrow plasma cells of myeloma patients without such manifestation, but it was increased in tumor site plasma cells of patients with extramedullary disease compared to bone marrow plasma cells of such patients (p<0.0001). Together, our data suggest connection between lower level of microRNA-130a and extramedullary disease and prompt further work to evaluate this miRNA as a marker of extramedullary disease in multiple myeloma.
Keywords: Gene Expression Regulation, Neoplastic; Male; MicroRNAs; prognóza; mikro RNA; regulace genové exprese u nádorů; Plasma Cells; Adult; Aged; dospělí; Multiple Myeloma; mužské pohlaví; senioři; lidé středního věku; senioři nad 80 let; lidé; ženské pohlaví; Humans; Bone Marrow; kostní dřeň; Aged, 80 and over; Prognosis; plazmatické buňky; mnohočetný myelom; Female; Biomarkers, Tumor; nádorové biomarkery; Middle Aged